Most Recent Data (2000). Statistics Canada. CANSIM: Society and Community - Rural Canada | Country: Canada | Province: Northwest Territories | Table: Canadian Community Health Survey (CCHS 1.1) urban-rural profile, by sex | Variable: 1 or more two-week disability days, Rural, Both sexes | Units: , 2000. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. Dataset-ID: 075-001-189. - Statistics Canada (Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc., 2015)
Statistics Canada (2015). CANSIM: Society and Community - Rural Canada | Country: Canada | Province: Northwest Territories | Table: Canadian Community Health Survey (CCHS 1.1) urban-rural profile, by sex | Variable: 1 or more two-week disability days, Rural, Both sexes | Units: , 2000. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. [Data-file]. Dataset-ID: 075-001-189. Dataset: Provides data on the rural economy, rural population trends, migration, and changing patterns in rural communities in Canada, including demography, health, education, manufacturing and labor, as well as households and families. CANSIM is Statistics Canada's key socioeconomic database. The datasets included here provide statistics on the Canadian population, and the nation’s resources, economy, society, and culture. In addition to conducting a Census every five years, approximately 350 active surveys are conducted on virtually all aspects of Canadian life. Statistics are provided for the nation as a whole, provinces, and other subnational geographies where available. Category: Population and Income Source: Statistics Canada Established as Canada's central statistical office by the Statistics Act of 1985, Statistics Canada is required to "collect, compile, analyse, abstract and publish statistical information relating to the commercial, industrial, financial, social, economic and general activities and conditions of the people of Canada." Its main objectives are to provide statistical information and analysis about Canada’s economic and social structure and to promote sound statistical standards and practices. http://www.statcan.gc.ca/ Subject: Rural Development, Rural Population, Rural Poverty, Sociodemographic Characteristics, Rural Areas